Field evaluation of a pressurized ozone treatment system to degrade sulfolane in contaminated groundwaters. Issue 5 (October 2020) - Khan, Muhammad Faizan; Yu, Linlong; Achari, Gopal
Graphical abstract: Highlights: Pilot-scale pressurized ozone system was effective in degrading sulfolane. Batch and continuous flow modes were consistent with first order kinetics. Pressurized ozone degraded sulfolane more efficiently with H2 O2. Intermittent ozone operation can improve conservation of ozone utilization. Abstract: Sulfolane, an industrial solvent, has consistently been reported as a persistent groundwater contaminant. In this research, a pilot-scale field investigation was conducted using a pressurized ozone treatment system installed on-site to study the degradation of sulfolane in three different contaminated groundwaters (pH > 7). The pressurized ozone system was utilized using batch and continuous flow modes to evaluate sulfolane degradation kinetics and augmentation of the oxidation process using various secondary chemicals (H2 O2, CaO2, CaO, and, NaOH). The batch study showed sulfolane degradation followed first order kinetics and this was consistent with results obtained using continuous flow mode. The addition of H2 O2 improved sulfolane degradation percentage from 68% to 74%. On the other hand, the combination of other chemicals with ozone did not augment the oxidation process in either batch or continuous modes. High concentrations of dissolved solids and other unidentified impurities in the groundwater played a crucial role in the efficacy of ozone treatment to degrade sulfolane. Furthermore, a 20% improvement in utilization of ozone was observed through intermittently sparged ozone injection which proved to be a viable option for field applications. Bromate concentrations higher than drinking water guidelines were detected in treated groundwater after ozone treatment which suggests the need for a polishing treatment step post ozonation.